Identification of the Conserved Sequences at the Species Level of Odontoglossum Ringspot Virus and Other Members of Tobamovirus by Its Coat Protein Sequence Analysis - Pattana Srifah; Nanyawan Rungroj; Surapee Keeratiyaangul (Agriculture and Natural Resources, 2006)
A synthetic 1056 base pair at 3′-terminal region of odontoglossum ringspot virus (ORSV) genome was determined by its amino acid sequence compositions. The deduced coat protein (CP) sequence of ORSV was compared with 32 available published data of tobamovirus CPs. The relationship of amino acid composition of tobamovirus CPs fell into three major clusters similar to the tobamovirus subgroups previously classified. The amino acid sequence within ORSV group showed highly conserved, almost 96-100% identical homology, but was distinct from the other tobamovirus subgroups. However, the topography of the phylogenetic tree showed that the orchid-infecting, crucifer-infecting (85-100% identity), some tomato-infecting (81-94% identity) and tobacco-infecting virus strains (95-98% identity) formed tight clusters which were mostly correlated with the host range preferences of the viruses. The application of the program clustalW to amino acid data alignment classified and identified the conserved sequence and genetic variability at the species level of each member of tobamovirus subgroups by its coat protein sequence analysis. According to the high degree of conservation in ORSV CP composition, it was successful in detecting virus infecting broad length of orchid host plants showing severe symptoms or appearing symptomless by RT-PCR with ORSV CP specific primers.